2009
DOI: 10.1111/j.1469-8137.2008.02755.x
|View full text |Cite
|
Sign up to set email alerts
|

Does photosynthesis affect grassland soil‐respired CO2 and its carbon isotope composition on a diurnal timescale?

Abstract: Summary• Soil respiration is the largest flux of carbon (C) from terrestrial ecosystems to the atmosphere. Here, we tested the hypothesis that photosynthesis affects the diurnal pattern of grassland soil-respired CO 2 and its C isotope composition (δ 13 C SR ).• A combined shading and pulse-labelling experiment was carried out in a mountain grassland. δ 13 C SR was monitored at a high time resolution with a tunable diode laser absorption spectrometer.• In unlabelled plots a diurnal pattern of δ 13 C SR was obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

31
236
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 250 publications
(268 citation statements)
references
References 48 publications
31
236
1
Order By: Relevance
“…Firstly, there might be a fast transport of recent photosynthesis and substrate supply from the canopy to the soil (Högberg et al, 2008;Bahn et al, 2009;Vargas et al, 2011a). High transport rates of assimilates from leaves into roots and their subsequent loss in the processes of root respiration have been demonstrated by previous laboratory experiments (e.g.…”
Section: Time Lag Between Gpp and Soil Respiration On A Diurnal Scalementioning
confidence: 91%
See 3 more Smart Citations
“…Firstly, there might be a fast transport of recent photosynthesis and substrate supply from the canopy to the soil (Högberg et al, 2008;Bahn et al, 2009;Vargas et al, 2011a). High transport rates of assimilates from leaves into roots and their subsequent loss in the processes of root respiration have been demonstrated by previous laboratory experiments (e.g.…”
Section: Time Lag Between Gpp and Soil Respiration On A Diurnal Scalementioning
confidence: 91%
“…The time lags of 0e4 h in our results are consistent with previous findings. For example, a free air CO 2 enrichment experiment (FACE) in a mixed deciduous forest showed that the diurnal cycle of soil respiration was correlated with PAR with a 1 h lag (Liu et al, 2006), and a pulselabelling experiment also showed that under sunny conditions photoassimilates in a mountain grassland were transported and respired belowground within less than 2 h (Bahn et al, 2009). More recently, soil respiration showed significant responses to plant photosynthetic activity with a time lag of about 0e3 h in a steppe ecosystem (Yan et al, 2011).…”
Section: Time Lag Between Gpp and Soil Respiration On A Diurnal Scalementioning
confidence: 99%
See 2 more Smart Citations
“…Högberg et al (2008) traced the fate of new C through various tree components, and into microbial pools. Most recently, Bahn et al (2009) reported an innovative study in which 13 C of soil respiration was measured by tunable diode laser absorption spectrometry (TDLAS). This combination of high-temporal resolution 13 C measurements of soil respiration (i.e.…”
Section: Isotope Approachesmentioning
confidence: 99%